2017
DOI: 10.1007/s11065-017-9343-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Neuropsychological Outcomes of Childhood Onset Acute Disseminated Encephalomyelitis (ADEM): a Meta-Analysis

Abstract: The long-term neurocognitive prognosis of childhood onset acute disseminated encephalomyelitis (ADEM) is unclear. This review and quantitative synthesis of the available literature examined whether there are long-term impacts of childhood ADEM on neurocognitive functioning. A search of online databases (MEDLINE, EMBASE, EBSCO CINAHL, PsycINFO and the Cochrane Database of Systematic Reviews) from their inception to October 2015 and reference lists identified 13 papers eligible for inclusion in the systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Our results are consistent with those of previous studies and support findings that the outcome of pediatric ADEM was more favorable than that of pediatric multifocal CIS [3,11,22,23]. On the other hand, other recent studies showed that there are lasting neurocognitive and psychosocial deficits including ADHD and epilepsy in pediatric ADEM, and even children who were considered to have fully recovered at discharge may be affected [17,24,25]. Our study also included two patients with ADHD or epilepsy, despite them achieving full recovery in the acute phase.…”
Section: Treatments and Outcomesupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with those of previous studies and support findings that the outcome of pediatric ADEM was more favorable than that of pediatric multifocal CIS [3,11,22,23]. On the other hand, other recent studies showed that there are lasting neurocognitive and psychosocial deficits including ADHD and epilepsy in pediatric ADEM, and even children who were considered to have fully recovered at discharge may be affected [17,24,25]. Our study also included two patients with ADHD or epilepsy, despite them achieving full recovery in the acute phase.…”
Section: Treatments and Outcomesupporting
confidence: 92%
“…3) abnormal lesions may not be identified on initial MRI, and 4) more than half of the patients have a rapid response to high-dose mPSL, will be useful for clinical management of pediatric ADEM. Sequelae at discharge (25) Motor paralysis (13) Cognitive dysfunction…”
Section: Treatments and Outcomementioning
confidence: 99%
“…A recent metaanalysis described an overall good long-term outcome after ADEM [6]. Nevertheless, fever on admission, ventilator-associated pneumonia, and meningism, as seen in our patient, seem to be associated with a poor outcome [7].…”
Section: Discussionsupporting
confidence: 41%
“…It appears that though most children appear to lack long-term sequela, some children suffer from ongoing neurocognitive deficits. 43 A subset of children who present with clinical demyelinating attacks has been found to have antibodies which bind myelin oligodendrocyte glycoprotein (MOG). In a cohort of 19 children with ADEM and 28 with clinically isolated syndrome, 19 (40%) were found to have anti-MOG antibodies.…”
Section: Acute Disseminated Encephalomyelitismentioning
confidence: 99%